2019
DOI: 10.1002/mp.13355
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing a novel scintillating glass for application to megavoltage cone‐beam computed tomography

Abstract: Purpose The purpose of this study was to evaluate the performance of a prototype electric portal imaging device (EPID) with a high detective quantum efficiency (DQE) scintillator, LKH‐5. Specifically, image quality in context of both planar and megavoltage (MV) cone‐beam computed tomography (CBCT) is analyzed. Methods Planar image quality in terms of modulation transfer function (MTF), noise power spectrum (NPS), and DQE are measured and compared to an existing EPID (AS‐1200) using the 6 MV beamline for a Vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This improved the robustness and transferrability of the model between institutions. Furthermore, recent research has been dedicated towards the improvement of detective quantum efficiency and contrast-tonoise ratio of the MV imager, which include the multi-layer imager (MLI) design (Myronakis et al 2017, Hu et al 2018, Harris et al 2020, 2021, pixelated scintillation (Star-Lack et al 2015) and advanced scintillation materials (Hu et al 2019). Harris et al (2021) demonstrated a 41.7% increase in marker tracking efficiency (number of frames that successfully track markers compared to maximum number of trackable frames) when using a novel multilayer MV imager.…”
Section: Discussionmentioning
confidence: 99%
“…This improved the robustness and transferrability of the model between institutions. Furthermore, recent research has been dedicated towards the improvement of detective quantum efficiency and contrast-tonoise ratio of the MV imager, which include the multi-layer imager (MLI) design (Myronakis et al 2017, Hu et al 2018, Harris et al 2020, 2021, pixelated scintillation (Star-Lack et al 2015) and advanced scintillation materials (Hu et al 2019). Harris et al (2021) demonstrated a 41.7% increase in marker tracking efficiency (number of frames that successfully track markers compared to maximum number of trackable frames) when using a novel multilayer MV imager.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we consider layer configurations that combine complementary detectors: one layer with high sensitivity and one with better spatial resolution. These particularly scintillators have been characterized in previous studies (Rottmann et al 2016, Hu et al 2019, and fabricated into development EPID panels, enabling future experimental validation. Furthermore, employing this weighting method may enable use of novel scintillator materials, which a priori are not suitable for a general-purpose planar imaging device by themselves, but potentially provide improved performance when combined with other layers with different responses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had validated this standard EPID model using Geant4 applications (Blake et al 2013, Myronakis et al 2016, Shi et al 2018. The bottom layer in configuration 1 (figure 1(a)) features a continuous slab of a 3.0mm thick LKH-5 scintillating glass (ρ = 3.85 g cm −1 ) while in configuration two (figure 1(b)) the scintillation glass matrix was based on the detector described by Hu et al (2019), which is composed of 12 mm thick individual blocks of LKH-5 with planar dimensions of 1.512 × 1.512 mm 2 with 20 μm separation (including glue and 88% reflective double-sided aluminum deposition Mylar). LKH-5 is a terbium doped glass with the following composition: oxygen (30%), barium (40%), silicon (20%) and terbium (10%) and it was modeled using the information provided by the manufacturer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable research has been devoted to improving EPIDs, in order to support advanced clinical applications. Investigators have explored different scintillation materials (Hu et al 2019), pixelated scintillators (Star-Lack et al 2015), and structured phosphors (Zhao et al 2004), for example. A cost-effective and easily implementable approach is to stack multiple layers of currently available components to improve photon collection without increasing Swank noise (Swank 1973).…”
Section: Introductionmentioning
confidence: 99%